Music, science, philosophy: Models in the universe of thought - Kassler, Jamie Croy (Aldershot Ashgate Variorum, 2002)
Model theory is not the main theme of this work. The main theme is the interrelatedness of knowledge, of which models are prime instances, since in most, if not all, of their functions, establishing relations means cutting across lines that traditionally demarcate such separate domains as science and music. For example, science can find its models from the technology and semantic field of music, music can find its models from the technology and semantic fields of science, and each domain may be guided by a philosophical or metaphysical principle. Therefore we have the title of this book, "Music, Science, Philosophy". But the text itself is structured as a mirror image of its title. Part 1, "Philosophy" (chapters 1-3), and Part 2, "Science" (chapters 4-6), provide instances of music's contribution to epistemology, logic and the early modern sciences of developmental biology ("generation"), continuum mechanics, anatomy and physiological psychology, whereas Part 3, "Music" (chapters 7-10), provides instances of what some other domains have given back to the philosophy and theory of music.